2014
DOI: 10.1089/cyber.2013.0338
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Networking Technologies on Female Religious Veil-Wearing Behavior in Iran

Abstract: Social networking technologies can influence attitudes, behaviors, and social norms. Research on this topic has been conducted primarily among early adopters of technology and within the United States. However, it is important to evaluate how social media might affect people's behaviors in international settings, especially among countries with longstanding, government recommended, cultural and religious traditions and behaviors, such as Iran. This study seeks to assess whether Iranian women who have been usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Perhaps, part of the reason for the lack of significance stemmed from the fact that these Iranians were part of a youthful generation that is becoming more “Westernized” (Abdollahyan, 2004; Azadarmaki, 2003; Moidfar, 2003). As described earlier, younger Iranian women and those more connected on social media were less likely to adhere to the tradition of wearing a veil (Young et al., 2014). Nevertheless, they were still more likely to choose religious figures as favorite celebrities than their American counterparts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Perhaps, part of the reason for the lack of significance stemmed from the fact that these Iranians were part of a youthful generation that is becoming more “Westernized” (Abdollahyan, 2004; Azadarmaki, 2003; Moidfar, 2003). As described earlier, younger Iranian women and those more connected on social media were less likely to adhere to the tradition of wearing a veil (Young et al., 2014). Nevertheless, they were still more likely to choose religious figures as favorite celebrities than their American counterparts.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Iran is in transition from an older, more religious, and conservative society to a younger one that is decidedly less religious and less conservative (Abdollahyan, 2004; Moidfar, 2003). For example, a recent study among Iranian women found that younger women and women who spend more time on social media were less interested in wearing a veil (Young, Shakiba, Kvok, & Montazeri, 2014). Because the present sample of Iranians is youthful, it is unclear how they will score collectively on some of the measures used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…According to research by Sean et al (2014), social media affects people's behaviors in global settings like Iran that follow government-recommended cultural and religious traditions and behaviors (Sean et al 2014). The offline, local reality has yet to fully reflect the online social movements.…”
Section: The Significance Of the Hijab Policy For Iranian Everyday Lifementioning
confidence: 99%
“…Rapidly, technological developments are the more sophisticated it has given birth to several innovations, one of which is the existence of social media that can connect people to one another (Young, Shakiba, Kwok, & Montazeri, 2014). Social media is currently very widely used not only as a medium of communication but also as a medium for da'wa (Zulhazmi & Hastuti, 2018).…”
Section: Introductionmentioning
confidence: 99%